2021
DOI: 10.3390/biom11030394
|View full text |Cite
|
Sign up to set email alerts
|

Recent Insights into Anthocyanin Pigmentation, Synthesis, Trafficking, and Regulatory Mechanisms in Rice (Oryza sativa L.) Caryopsis

Abstract: Anthocyanins are antioxidants used as natural colorants and are beneficial to human health. Anthocyanins contribute to reactive oxygen species detoxification and sustain plant growth and development under different environmental stresses. They are phenolic compounds that are broadly distributed in nature and are responsible for a wide range of attractive coloration in many plant organs. Anthocyanins are found in various parts of plants such as flowers, leaves, stems, shoots, and grains. Considering their nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 143 publications
2
31
0
Order By: Relevance
“…Though the exact genetic basis of coloration in organs remains unclear, there are reports predicting that the C1 locus might regulate the tissue-specific expression in black rice varieties. The R2R3-MYB might act as a potential activator of DFR and ANS involved in the ABP, mainly during hull pigmentation (Mackon et al, 2021). Interestingly, in the present study, OsC1 showed a coordinated expression pattern with the late ABP structural genes, indicating its involvement in regulating the pathway.…”
Section: Reduced Membrane Damage Observed Insupporting
confidence: 43%
“…Though the exact genetic basis of coloration in organs remains unclear, there are reports predicting that the C1 locus might regulate the tissue-specific expression in black rice varieties. The R2R3-MYB might act as a potential activator of DFR and ANS involved in the ABP, mainly during hull pigmentation (Mackon et al, 2021). Interestingly, in the present study, OsC1 showed a coordinated expression pattern with the late ABP structural genes, indicating its involvement in regulating the pathway.…”
Section: Reduced Membrane Damage Observed Insupporting
confidence: 43%
“…High expression of anthocyanin pathway genes leads to a high accumulation of anthocyanins [ 4 , 6 ]. Ectopic expression of CHS gene from rice and UDP-GLUCOSYL TRANSFERASE gene from citrus triggers the anthocyanin and proanthocyanidins accumulation in rice and transgenic Arabidopsis , respectively [ 4 , 27 , 28 ]. The Arabidopsis leucoanthocyanidin dioxygenase ( LDOX ) is required for vacuole development and proanthocyanidin synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Kushwaha et al (2020) reported that temperate climate could favor the rise in grain's anthocyanin content than the warm climate. In addition, the increase in the color intensity was increase the total anthocyanin content (Mackon et al 2021). Moreover, the color intensity and pericarp thickness had affected to anthocyanin content in rice pericarp.…”
Section: Nutritional Value and Antioxidant And Antidiabetic Activitiesmentioning
confidence: 97%